Tratados de paz, grupos étnicos y territorios en disputa a fines del siglo XVIII - Nacuzzi, Lidia R. (2006)
The article poses new readings about the peace treaties signed in the Chaco and Pampa regions during the late 18 century, analyzing those pacts as regulators of white-Indian realtionships in frontiers where the Crown did not control effectively the situation and indigenous groups were still independent. th